DNA Methylation Identifies Loci Distinguishing Hereditary Nonpolyposis Colorectal Cancer Without Germ‐LineMLH1/MSH2Mutation from Sporadic Colorectal Cancer. Issue 12 (December 2016) - Chen, Chung‐Hsing; Jiang, Shih Sheng; Hsieh, Ling‐Ling; Tang, Reiping; Hsiung, Chao A; Tsai, Hui‐Ju; Chang, I‐Shou
Abstract : OBJECTIVES: : Roughly half of hereditary nonpolyposis colorectal cancer (HNPCC) cases are Lynch syndrome and exhibit germ‐line mutations in DNA mismatch repair (MMR) genes; the other half are familial colorectal cancer (CRC) type X (FCCTX) and are MMR proficient. About 70% of Lynch syndrome tumors have germ‐line MLH1 or MSH2 mutations. The clinical presentation, histopathological features, and carcinogenesis of FCCTX resemble those of sporadic MMR‐proficient colorectal tumors. It is of interest to obtain biomarkers that distinguish FCCTX from sporadic microsatellite stable (MSS) CRC, to develop preventive strategies. METHODS: : The tumors and adjacent normal tissues of 40 patients with HNPCC were assayed using the Illumina Infinium HumanMethylation27 (HM27) BeadChip to assess the DNA methylation level at about 27, 000 loci. The germ‐line mutation status of MLH1 and MSH2 and the microsatellite instability status in these patients were obtained. Genome‐wide DNA methylation measurements of three groups of patients with general CRC were downloaded from public domain databases. Probes with DNA methylation levels that differed significantly between patients with sporadic MSS CRC and FCCTX were examined, to explore their potential as biomarkers. RESULTS: : We found that MSS HNPCC tumors were overwhelmingly hypomethylated compared with those from patient groups with other types of CRC, including germ‐line MLH1/MSH2 ‐mutated HNPCC and sporadic MSS CRC. Five gene‐marker panels that exhibited a sensitivity of 100% and a specificity higher than 90% in both discovery and validation cohorts were proposed to distinguish MSS HNPCC tumors from sporadic MSS CRC. CONCLUSIONS: : Our results warrant further investigation and validation. The loci identified here may become useful biomarkers for distinguishing between FCCTX and sporadic MSS CRC tumors.